1987
DOI: 10.1038/hdy.1987.34
|View full text |Cite
|
Sign up to set email alerts
|

Differential mating success in populations of seaweed flies (Coelopa frigida)

Abstract: The reproductive success of seaweed flies (Coelopa frigida) was studied in natural populations. The sizes of females, both mothers and those not producing eggs, as well as of the males available to be fathers, were estimated from their wing lengths. The animals were also classified for their genotype at the alcohol dehydrogenase (Adh) locus-a polymorphic locus tightly associated with a large chromosomal inversion. The fathers' genotypes were inferred from the genotypes of the mother and her offspring. Males of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…In mass matings female success wa:s homogeneous whereas heterogeneity was observed between genotypes among the results reported here. Furthermore, the pattern of mating was predominantly negatively assortative in the results of Day and Butlin (1987) whereas in the present experiments the flies tended to exhibit positive assortment.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…In mass matings female success wa:s homogeneous whereas heterogeneity was observed between genotypes among the results reported here. Furthermore, the pattern of mating was predominantly negatively assortative in the results of Day and Butlin (1987) whereas in the present experiments the flies tended to exhibit positive assortment.…”
Section: Discussioncontrasting
confidence: 36%
“…1985) and larval survival (Butlin et aL, 1984). There is also differential male mating success between genotypes (Butlin et a!., 1982b; and populations exhibit negative assortative mating with respect to the af3 inversion (Day and Butlin, 1987). A recent analysis of mating (Crocker and Day, 1987) suggested that female seaweed flies might be choosing their mates on the basis of inversion genotype, and that there might, in addition, be an element of male choice.…”
mentioning
confidence: 99%
“…Inversion frequencies in natural populations strongly suggest that the polymorphism is maintained by selection, and laboratory experiments indicate that at least three types of selection may operate: heterokaryotypic advantage in egg to adult viability (Butlin et a!., 1984), variation in development time (Day et a!., 1980), and sexual selection (Butlin et a!., 1982b, Day et a!., 1987. This is therefore a promising system in which to study the connection between environmental parameters and inversion frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The materials and experimental procedures are fully described in the accompanying paper (Day et a!., 1987).…”
Section: And Methodsmentioning
confidence: 99%
“…Finally, Bateson (1983) (Butlin et aL, 1982a;Day et a!., 1987), and also significant differences in the fecundities of individuals (Butlin et aL, 1985). This report is concerned with a further aspect of reproductionwho mates with whom?…”
Section: Introductionmentioning
confidence: 99%